UWOLNIENIE MICHAIŁA CHODORKOWSKIEGO: NOWY ETAP LIBERALIZACJI ROSJI? - Ilnicki, Marek (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article relates to the results of pardoning the founder of Jukos oil company Mikhail Khodorkovsky by the Russian President Vladimir Putin. The author has lied down a broad analysis of possible causes of Russian President’s decission as well as shown the legal basis in force in this country, regulating the procedure of a pardon. According to contemporary practice, a plea for pardon was considered as same to a confession to commiting a crime, what was what neither Khodorkovski nor his partner wanted to do. According to the author the compromise was reached; Russian regulations demands for personally formulated a plee for pardon, however confession to a crime is no longer an obligatory element of the procedure. Among possible causes for releasing Khodorkovsky there were mentioned such factors as: an attempt to improve the image of Russia before the inauguration of Winter Games in Sochi; establishing the lack of validation of accusations of breaking the human rights in discussed case; shifting a focus of public opinion from deterorating geopolitical situation of the Russian Federation; an attempt to mute the voices of the opposition which was trying to bring down the myth of President Putin’s diplomatic successes; or an attempt to demonstrate special political bounds between Russia and Germany, which participated in the release of Khodorkovsky. The author also underlined the fact that the release of Khodorkovsky was not connected to the amnesty of prisoners announced by the State’s Duma on the occasion of the 20’th anniversary of the Russian Constitution. According to the author the latest political changes in Russia prove the theories about a need to improve the image. In the article there was also included a broad analysis of a taxation system concerning the largest Russian oil companies in 2000–2001 and pointed out the possible motives of Khodorkovsky’s arrestment. According to the author the surprising issue is not a constatnt support of the Russian society to the government, but the behaviour of the influential Russian businessmen and liberal polititians.